Magnetic ground state of an individual Fe(2+) ion in strained semiconductor nanostructure - Smoleński, T. (Nat Commun, 2016)
Single impurities with nonzero spin and multiple ground states offer a degree of freedom that can be utilized to store the quantum information. However, Fe(2+) dopant is known for having a single nondegenerate ground state in the bulk host semiconductors and thus is of little use for spintronic applications. Here we show that the well-established picture of Fe(2+) spin configuration can be modified by subjecting the Fe(2+) ion to high strain, for example, produced by lattice mismatched epitaxial nanostructures. Our analysis reveals that high strain induces qualitative change in the ion energy spectrum and results in nearly doubly degenerate ground state with spin projection S(z)=±2. We provide an experimental proof of this concept using a new system: a strained epitaxial quantum dot containing individual Fe(2+) ion. Magnetic character of the Fe(2+) ground state in a CdSe/ZnSe dot is revealed in photoluminescence experiments by exploiting a coupling between a confined exciton and the single-iron impurity. We also demonstrate that the Fe(2+) spin can be oriented by spin-polarized excitons, which opens a possibility of using it as an optically controllable two-level system free of nuclear spin fluctuations.